Penataan Permukiman Kumuh Rawan Bencana Kebakaran di Kelurahan Lingkas Ujung Kota Tarakan - Oktaviansyah, Evans (Jurnal Tata Kota dan Daerah, 2012)
Unbalance condition between land supply and the growth of urban activities will cause a settlement problem. This conditions also happened in coastal zone of Tarakan which resulting the slum areas. The purposes of this research are to indentify the characteristics, to evaluate the vulnerability of fire hazard and find the solutions for the slum problem in Lingkas Ujung, Tarakan. The research uses descriptive- evaluative approach, and the main analysis is the ‘scoring method’ for identifying the slum and fire hazard areas. The results are 1) The slum areas of Lingkas Ujung Tarakan are classified into coastal slum area, which most of them are floating houses. 2) The areas which calssified into slum area have high vulnerability of fire hazard. This condition affected by the building density and building structure. The area categorized the worst slum are block (rukun tetangga) 6 and 11, and the other categorized medium slum. Block 1 is not categorized into slum area, because this block has low population and density bulding.The vulnerability of fire hazard in Lingkas Ujung affected by building density, accessibility, building structure and water resource. The block categorized into high risk of fire hazard are block 2, 3, 8, 14, 16 and 18. 3) The solutions of slum area in Lingkas Ujung Tarakan are; short term approach purpose to solve the fire risk, waste management and sanitation, long time approach purpose to redesign the area, using land consolidation.Keywords: Slum Area, Fire Hazard